Pemasangan Solar Panel Untuk Sistem Charging Power Station di Kawasan Ekowisata Gunung Kuta, Kabupaten Bogor - Goeritno, Arief; Maulana, Muhammad Azril; Shulhan, Fauzan; Fiqwananda, Hakim (Mitra Teras: Jurnal Terapan Pengabdian Masyarakat, 2023)
Abstract Installing solar panels to obtain electrical power through the implementation of Community Service Program (CSP, Kuliah Kerja Nyata, KKN) activities is a form of effort to exploit electrical resources. Since it is still very difficult to find electrical power in open areas in ecotourism areas, this KKN activity can provide the resources that the community in the Ecotourism Area of Gunung Kuta, Cibadak Village, Sukamakmur Subdistrict, District of Bogor, Province of Jawa Barat, really needs. The implementation of the installation of solar panels for the charging power station (CPS) system is based on two activity implementation targets, namely (a) the assembly and installation of the CPS system and (b) the creation of electrical cable installation routes and the utilization of electrical power. The activity implementation method is in the form of six work steps in sequence to achieve two targets, namely (i) installation of solar panels, (ii) placement of solar charge controllers (SCC) and single-phase inverters, (iii) placement of control panels, (iv) installation and placement of batteries, (v) creation of cable routes for electrical power installations, and (vi) installation of electrical loads and observation of loading times. The results of activities related to the first activity target (assembly and installation of the CPS system) include (a) the installation and placement of solar panels with support poles on community agricultural land locations with connection via 2 x 1.5 mm2 electrical power cables because they are separate from the placement control panel at a distance of fifty meters; (a2) the installation of a solar charge controller (SCC) and single-phase inverter on the control panel; (a3) the placement of |83Mitra Teras: Jurnal Terapan Pengabdian MasyarakatVolume 2Nomor2, Desember2023the control panel in a special place protected from heat and rain; and (a4) the installation and battery placement to provide electrical power in a stable condition and for a long time. For implementation related to the second activity target (creating electrical cable installation routes and utilizing electrical power), including (b1) creating electrical installations with 2 x 1.5 mm2 electrical power cables and installing a number of points for lighting lamps and contact boxes (outlets) for charger purposes, (b2) observation of the solar panel system when there are electrical loads in the form of light-emitting diode (LED) type lamps and loading from the charger system for a number of mobile phones Based on the results and discussion, it can be concluded that the achievement of installing solar panels and charge controllers that are integrated with batteries and inverters, then connected to the electrical power cable installation route, and providing power for electrical loads is the result of activities that can be used for local lighting and charging batteries. Abstrak Pemasangan panel surya untuk perolehan daya listrik melalui pelaksanaan kegiatan Kuliah Kerja Nyata (KKN) merupakan bentuk sebuah upaya untuk pengusahaan sumber daya listrik. Keberadaan daya listrik di ruang terbuka kawasan ekowisata masih sangat sulit ditemukan, sehingga melalui kegiatan KKN ini dapat disediakan sumberdaya yang sangat dibutuhkan oleh masyarakat di Kawasan Ekowisata Gunung Kuta, Desa Cibadak, Kecamatan Sukamakmur, Kabupaten Bogor, Provinsi Jawa Barat. Pelaksanaan pemasangan panel surya untuk keperluan sistem Charging Power Station (CPS) didasari oleh dua sasaran pelaksanaan kegiatan, yaitu (a) perakitan dan pemasangan sistem CPS dan (b) pembuatan jalur instalasi kabel listrik dan pemanfaatan daya listrik. Metode pelaksanaan kegiatan berupa enam langkah pengerjaan dengan urutan untuk pencapaian dua sasaran, yaitu (i) pemasangan solar panel, (ii) penempatan solar charge controller (SCC) dan inverter fase-tunggal, (iii) penempatan panel kontrol, (iv) pemasangan dan penempatan baterai, (v) pembuatan jalur kabel untuk instalasi daya listrik, dan (vi) pemasangan beban-beban listrik dan pengamatan saat pembebanan. Hasil kegiatan terkait dengan sasaran kegiatan pertama (perakitan dan pemasangan sistem CPS), meliputi (a1) pemasangan dan penempatan solar panel dengan tiang penyangga pada lokasi lahan pertanian masyarakat dengan penghubungan melalui kabel daya listrik ukuran 2 x 1,5 mm2, karena terpisah dari penempatan panel kontrol dengan jarak lima puluh meter, (a2) pemasangan solar charge controller (SCC) dan inverter fase-tunggal pada panel kontrol, (a3) penempatan panel kontrol di tempat khusus yang terlindungi dari kondisi panas dan hujan, dan (a4) pemasangan dan penempatan baterai, agar penyediaan daya listrik dengan kondisi stabil dan dalam waktu lama. Untuk pelaksanaan yang berkaitan dengan sasaran kegiatan kedua (pembuatan jalur instalasi kabel listrik dan pemanfaatan daya listrik), meliputi (b1) pembuatan instalasi listrik dengan kabel daya listrik ukuran 2 x 1,5 mm2 dan pemasangan sejumlah titik untuk lampu penerangan dan kotak kontak (outlet) untuk keperluan charger, (b2) pengamatan terhadap sistem solar panel ketika terdapat beban-beban listrik berupa lampu jenis light emitting diode (LED) dan pembebanan dari sistem charger untuk sejumlah telepon genggam. Berdasarkan hasil dan diskusi dapat ditarik kesimpulan, bahwa ketercapaian pemasangan solar panel dan charge controller yang diintegrasikan dengan baterai dan inverter, selanjutnya dihubungkan ke jalur instalasi kabel daya listrik dan pemberian daya untuk beban-beban listrik merupakan hasil kegiatan yang dapat digunakan untuk penerangan setempat dan pengisian baterai.